Ngurup Cimplung: Food Security Strategy in Banjarnegara Household - Nurul Friska Dewi (UIN Maulana Malik Ibrahim Malang, 2019)
This study aims to look at the lives of farmers from a survival strategy perspective. An ethnographic approach is used with participant observation and interviews. The results of the study show that despite changes due to modernization of agriculture, local traditions and knowledge are still carried out. There are at least two strategies that are carried out in overcoming food security in their households, namely the short-term strategy, done by “ngurup cimplung”, taking plants around that can be used for daily needs. Whereas the long-term strategy is done by carrying out various rituals, namely “gethekan”, “Ujungan Ritual”, as well as istisqa prayers, all of which are to wish the Divine pleasure to keep nature-friendly with them. The strategy of performing this ritual also has a large function in food security both at the community and household level and even at the individual level. Each special event usually serves local food. For them, the efforts made are as an exchange effort, as “ngurup cimplung” is an economic exchange effort. Performing rituals by presenting a variety of foods are believed to get an equivalent fortune even more abundant than that given. Although rice is a staple food in every activity, the people of Gumelem, Banjarnegara can still use it wisely as a food security effort.Penelitian ini bertujuan untuk melihat kehidupan petani dari perspektif survival strategy. Pendekatan etnografi digunakan dengan teknik observasi partisipan dan wawancara. Hasil studi menunjukkan meskipun terjadi perubahan akibat modernisasi pertanian, tetapi tradisi dan pengetahuan lokal tetap dilakukan. Ada dua strategi yang dilakukan petani yaitu strategi jangka pendek yaitu dengan “ngurup cimplung”, mengambil tanaman di sekitar yang bisa dimanfaatkan untuk kebutuhan sehari-hari. Sedangkan strategi jangka panjang dilakukan dengan melakukan berbagai ritual, yaitu “gethekan”, ritual adat ujungan, maupun sholat istisqa yang kesemuanya adalah mengaharap ridha Ilahi agar alam tetap bersahabat dengan mereka. Dengan melakukan ritual ini juga memiliki fungsi besar dalam ketahanan pangan baik di level komunitas maupun rumah tangga bahkan individu. Setiap kegiatan khusus biasanya menyuguhkan pangan lokal. Bagi mereka, upaya yang dilakukan adalah sebagai upaya pertukaran, sebagaimana “ngurup cimplung” merupakan upaya pertukaran ekonomi. Sedangkan melakukan ritual dengan menyuguhkan berbagai makanan dipercaya akan mendapatkan rejeki yang setara bahkan lebih berlimpah dari yang diberikan. Meskipun beras menjadi makanan pokok di setiap aktivitas, tetapi masyarakat Gumelem, Banjarnegara tetap bisa menggunakan dengan bijak sebagai upaya ketahanan pangan.